Serum testosterone and sex hormone–binding globulin are inversely associated with leucocyte telomere length in men: a cross-sectional analysis of the UK Biobank study. Issue 2 (8th February 2023) - Marriott, Ross J; Murray, Kevin; Budgeon, Charley A; Codd, Veryan; Hui, Jennie; Arscott, Gillian M; Beilby, John P; Hankey, Graeme J; Wittert, Gary A; Wu, Frederick C W; Yeap, Bu B
Abstract: Objective: Older men on an average have lower testosterone concentrations, compared with younger men, and more age-related comorbidities. Whether lower testosterone concentrations contribute to biological ageing remains unclear. Shorter telomeres are a marker for biological age. We tested the hypothesis that testosterone concentrations are associated with leucocyte telomere length (LTL), in middle- to older-aged men. Design: Cross-sectional analysis of the UK Biobank study, involving community-dwelling men aged 40-69 years. Methods: Serum testosterone and sex hormone–binding globulin (SHBG) were assayed. Free testosterone was calculated (cFT). Leucocyte telomere length was measured using polymerase chain reaction. Multivariable models were used to assess associations of hormones with standardised LTL. Results: In 167 706 men, median age 58 years, adjusting for sociodemographic, lifestyle, and medical factors, total testosterone was inversely associated with standardised LTL, which was 0.09 longer (95% confidence interval [CI], 0.08-0.10, P < .001) in men with total testosterone at median of lowest quintile [Q1] vs highest [Q5]. This relationship was attenuated after additional adjustment for SHBG (0.03 longer, CI = 0.02-0.05, P = .003). The association between cFT and LTL was similar in direction but lower in magnitude. In multivariable analysis, SHBG was inversely associated with standardised LTL, which was 0.12 longer (CI = 0.10-0.13, P < .001) for SHBG at median Q1 vs Q5. Results were similar with testosterone included in the model (0.10 longer, CI = 0.08-0.12, P < .001). Conclusions: Total testosterone and SHBG were independently and inversely associated with LTL. Men with higher testosterone or SHBG had shorter telomeres, arguing against a role for testosterone to slow biological ageing in men.